Engineering Properties of Concrete Made with Coal Bottom Ash as Sustainable Construction Materials - Fanny Monika; Hakas Prayuda; Martyana Dwi Cahyati; Erwiena Nurmala Augustin; Hilal Aulia Rahman; Agustin Dwi Prasintasari (Salehan Institute of Higher Education, 2022)
Concrete is considered one of the construction materials that contribute the most significant carbon dioxide in the world. Meanwhile, according to various studies, concrete production will continue to rise through 2050, especially in developing countries. According to several reports, cement manufacture is one of the largest sources of carbon dioxide in the concrete sector. In addition, overexploitation of aggregates due to concrete production also causes unavoidable natural damage. Bottom ash waste was used as a replacement for cement and fine aggregate as sustainable construction materials. It is envisaged that this research would allow industrial waste to be utilized to its full potential, resulting in a concrete that is more environmentally friendly and minimizes carbon dioxide emissions during the manufacturing process. This study is divided into bottom ash as a cement substitute and bottom ash as a fine aggregate substitute. The engineering properties of the concrete were checked during the experiments in this study when it was fresh and hardened states. The slump test is used to determine the workability of fresh concrete. While for the hardened properties tests consist of compressive strength, splitting tensile strength, flexural strength, and mass density. The usage of bottom ash as a cement replacement demonstrates that as the composition of bottom ash increases, the performance of the hardened properties of concrete decreases. While using bottom ash as a fine aggregate replacement reveals that the performance of hardened properties has improved as the proportion of bottom ash utilized has increased. Doi: 10.28991/CEJ-2022-08-01-014 Full Text: PDF